ANALYSIS OF ONLINE PURCHASE INTENTION FROM THE PERSPECTIVE OF ONLINE CUSTOMER REVIEWS, ONLINE ADVERTISING, AND WEBSITE QUALITY - Abdullah, Muhamad Al Faruq; Pangaribuan, Yanthy Herawaty; Fathihani, Fathihani; Febrian, Wenny Desty (Jurnal Perspektif Manajerial dan Kewirausahaan (JPMK), 2022)
This study was conducted with the aim of knowing the effect of the variable relationship that affects purchase intention on e-commerce sites which is currently increasing. This research was conducted on one of the e-commerce sites, namely Elevenia. The data used is primary data using a questionnaire distributed to 120 respondents in DKI Jakarta and already know the Elevenia site. The data were analyzed using the Structural Positive and Equation Model (SEM) Partial Least Square (smartPLS 3.0) application to examine all the relationships between online consumer reviews, online advertising, and website quality variables on purchase intention in the model. The results of this study indicate that online consumer reviews and website quality have a positive and significant relationship with purchase intention. However, online advertising has a positive and insignificant relationship with purchase intention.